(untitled) (CIPEEX, 2025)
Improper credit instruments are those that do not apply the principles of traditional credit instruments—that is, they lack literality, legality, and autonomy, yet are relevant to business practices. Given constant historical transformations and the advent of the digital age, there is a growing emphasis on the use of these instruments, driven by the dematerialization of financial assets and the need for greater agility in commercial transactions. The electronic application of these instruments, however, faces challenges such as the lack of typical circulation, legal requirements for validity, and legal security issues. Despite this, digitalization offers opportunities, such as process simplification, cost reduction, and integration with banking systems and technology platforms. This summary aims to clarify and analyze the importance of improper credit instruments in the current context, highlighting the advantages and challenges in a context of growing technological innovation. The research was conducted using a bibliographic method and analysis of texts, doctrines, and laws related to the topic, consisting of a systematic reflective process. Traditional credit instruments cannot effectively keep up with digital transformations and the advancement of commercial relations, in addition to the exercise of formality and potential financial risks. Consequently, improper credit instruments have emerged, such as exchange contracts, book-entry duplicates, electronic checks, and digital promissory notes. With the digital transformation, these instruments are now issued, circulated, and executed electronically, reducing costs and optimizing processes, thus providing more efficient and secure means. However, there are many challenges to be addressed and important points that require special attention from legislators. The lack of paperwork and the complete dematerialization of securities require an efficient system to prevent fraud and duplicate issuances. Furthermore, the lack of specific regulations for some securities is noteworthy, creating legal uncertainty and compromising the trust of the parties in transactions. It can be concluded that the use of improper credit securities in the digital age represents an important step toward the modernization of commercial relations, but requires a balance between innovation and legal certainty. The digitalization of these instruments offers advantages, such as speed and cost reduction, but requires effective regulation and technological mechanisms that guarantee the authenticity and integrity of transactions.